Gabon : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the Request for Stand-By Arrangement on Gabon highlights economic developments and policies. A higher-than-anticipated rise in oil GDP more than offset lower-than-expected growth of non-oil GDP. Overall fiscal performance was strong, as the non-oil primary deficit was reduced by 8.6 percentage points to 8.2 percent of non-oil GDP in 2003. The authorities have strengthened their medium-term program to address the weaknesses in public finances that came to the fore under the staff-monitored program (SMP) and to tackle the impediments to private sector development while improving social indicators.